Associação da ocorrência do Ectima Contagioso (Orf vírus) em ovinos com seus cuidadores - Ferreira, Bruna Lapenna Sanches [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Responsible for significant economic losses in affected flocks, the Contagious Ecthyma is a disease caused by Orf virus belonging to the genus Parapoxvirus, epitheliotropic, the Poxviridae family and subfamily Chordopoxvirinae. It could be transmitted to humans who handle and work with infected sheep, causing crusted lesions and proliferative skin and the mucocutaneous junction, both in animals and in humans. The study showed the disease diffusion in São Paulo. They sampled 42 (8.64%) Animal caregivers and 444 (91.36%) sheep (n = 486). Of these, 453 (93.21%) showed no clinical signs, while 33 (6.79%) suspected cases of the disease (32 sheep and a caregiver) that were biopsied and performed histopathological and PCR tests. This all samples (n = 486) were suggestive of Ecthyma Contagious 6.38% and 0.41% suggestive of other skin lesions on histopathological examination. In examining PCR among 486 sampled, 4.32% were positive, while 2.47% were negative. The prevalence of reagents for virus neutralization was 67% in sheep and their caregivers 76% (p = 0.22). The distribution of titles had statistically significant differences between species with p = 0.0048. All surveyed 486 samples were negative in PCR test blood. The prevalence of animals with crust resulted in 7.2% and 2.4% their caregivers. Statistical analyzes were performed with SAS software (SAS Institute, 2011) at 0.05 significance level. Virus neutralization test in conclusion serum between species was statistically significant (p = 0.048), therefore, it is suggested that the higher the coexistence of sheep with their caregivers; the correlation between the diagnostic methods of virus neutralization, PCR and histopathology are important associations for the conclusive diagnosis of the disease; the disease is widespread in São Paulo and the geographical distribution did not influence the genetic similarity of the virus

Responsável por perdas econômicas significativas nos rebanhos afetados, o Ectima Contagioso é uma enfermidade causada pelo Orf vírus pertencente ao gênero Parapoxvirus, epiteliotrófico, da família Poxviridae e subfamília Chordopoxvirinae. Pode ser transmitida a humanos que manipulam e trabalham com ovinos infectados, causando lesões crostosas e proliferativas na pele e nas junções mucocutâneas, tanto em animais como em humanos. O estudo evidenciou a difusão da enfermidade no Estado de São Paulo. Foram amostrados 42 (8,64%) cuidadores de animais e 444 (91,36%) ovinos (n=486). Dentre estes, 453 (93,21%) não apresentaram sinais clínicos, enquanto que 33 (6,79%) casos suspeitos da doença (32 ovinos e um cuidador) que foram biopsiados e realizados os testes histopatológicos e de PCR. Deste total amostrado (n= 486), foram sugestivos para Ectima Contagioso 6,38% e 0,41% sugestivos para outras lesões de pele no exame histopatológico. No exame de PCR dentre os 486 amostrados, 4,32% foram positivas, enquanto 2,47% apresentaram resultado negativo. A prevalência de reagentes por virusneutralização foi de 67% nos ovinos e em seus cuidadores de 76% (p= 0,22). A distribuição dos títulos teve diferença estatística significativa entre as espécies com p = 0,0048. Todas as 486 amostras pesquisadas, foram negativas no exame de PCR do sangue. A prevalência de animais com crosta resultou em 7,2% e em seus cuidadores 2,4%. As análises estatísticas foram realizadas com o programa SAS (SAS Institute, 2011) em nível de significância de 0,05. Concluiu-se teste de virusneutralização no soro entre as espécies foi significativo estatisticamente (p = 0,048), com isso, sugere-se que quanto maior a convivência dos ovinos com seus cuidadores; a concordância entre os métodos diagnósticos de virusneutralização, PCR e histopatológico são importantes associações para o diagnóstico conclusivo da doença; a enfermidade está difundida no...
Occurrence of the Association of Ecthyma Contagious (Orf vírus) in sheep and their caregivers
Keywords: Ovino - Doenças; Pele - Doenças; Doenças transmissiveis; Dermatite de contato - Diagnóstico; Zoonoses; Reação em cadeia da polimerase; Contact dermatitis; Sheep